1987
DOI: 10.1200/jco.1987.5.12.1890
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-guided irradiation of advanced ovarian cancer with intraperitoneally administered radiolabeled monoclonal antibodies.

Abstract: Twenty-four patients with persistent epithelial ovarian cancer after chemotherapy with or without external beam irradiation, were treated with intraperitoneally administered 131I-labeled monoclonal antibodies HMFG1, HMFG2, AUA1, H17E2, directed against tumor-associated antigens. Acute side effects were mild abdominal pain, pyrexia, diarrhea, and moderate reversible pancytopenia. One patient developed a subphrenic abscess requiring surgical drainage. Eight patients with large volume disease, ie, greater than 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(74 citation statements)
references
References 37 publications
0
74
0
Order By: Relevance
“…It was also found that treated patients developed anti-DOTA (Kosmas et al, 1990) and anti-CITC-DTPA antibodies. All patients developed human antimouse antibodies as previously reported (Epenetos et al, 1987;Stewart et al, 1989). The difference in toxicity and immunogenicity between DTPA and DOTA linkage between antibody and radionuclide as well as the HAMA levels are reported elsewhere (Kosmas et al, 1992;Maraveyas et al, 1993).…”
Section: Toxicitymentioning
confidence: 72%
See 2 more Smart Citations
“…It was also found that treated patients developed anti-DOTA (Kosmas et al, 1990) and anti-CITC-DTPA antibodies. All patients developed human antimouse antibodies as previously reported (Epenetos et al, 1987;Stewart et al, 1989). The difference in toxicity and immunogenicity between DTPA and DOTA linkage between antibody and radionuclide as well as the HAMA levels are reported elsewhere (Kosmas et al, 1992;Maraveyas et al, 1993).…”
Section: Toxicitymentioning
confidence: 72%
“…The administered dose of radioactivity was measured in a SIEL isotope calibration chamber that had been calibrated with an yttrium-90 source (Stewart et al, 1990). Pharmacokinetics Pharmacokinetics, toxicity and dosimetry have been previously reported (Epenetos et al, 1987;Stewart et al, 1989Stewart et al, , 1990Maraveyas et al, 1993). Approximately 30% of the intraperitoneally injected immunoconjugate was absorbed into the systemic circulation by 48 h after administration (Stewart et al, 1989(Stewart et al, , 1990Maraveyas et al, 1993).…”
Section: Sunmnarymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of monoclonal antibodies (MAbs) for diagnosis (Cuttitta et al, 1984), imaging (Mach et al, 1981;Smedley et al, 1983) and now therapy (Lobuglio et al, 1986;Epenetos et al, 1987) of malignant disease is an increasingly realistic objective. MAbs generated against surface antigens of SCC can be divided according to the nature and expression of their target antigens into five main clusters, as defined at the International Workshop on SCC, London 1987 (Souhami et al, 1988).…”
mentioning
confidence: 99%
“…A further problem associated with the use of MAbs in patients compared with animals is the difference in the volume of distribution of the radioimmunoconjugate, potentially reducing the ability of MAbs to target to tumour. To attempt to overcome these problems several groups have concentrated their efforts on administering antibodies into body compartments that contain relatively small amounts of diffuse tumour (Epenetos et al, 1987;Lashford et al, 1988).…”
mentioning
confidence: 99%